Peran Pendidikan Karakter Berbasis Filsafat dalam Pencegahan Bullying di Lingkungan Pendidikan: A Systematic Literature Review - Shinta Dwi Handayani; Ema Rachmawati; Henny Suharyati; Chatarina Febriyanti; Ari Irawan (SAP (Susunan Artikel Pendidikan), 2026)
Bullying in educational settings is a serious issue that negatively affects students’ psychological, social, and academic development. Although various interventions have been implemented, reactive and administrative approaches have proven insufficient to prevent bullying sustainably. This study aims to systematically analyze the role of philosophy-based character education in preventing bullying in educational environments, as well as to identify prevailing value theories, implementation challenges, and future research prospects. This research employed a Systematic Literature Review (SLR) method following the PRISMA framework. Literature searches were conducted in the Scopus database in December 2025 using keywords related to character education, bullying, and philosophy of education. From 2,559 identified articles, 13 studies met the inclusion criteria and were analyzed qualitatively. In addition, bibliometric analysis using VOSviewer was applied to map conceptual relationships and research trends. The findings indicate that moral philosophy and virtue ethics constitute the dominant foundations for character education programs, supported by the concepts of moral agency, moral identity, and Social Emotional Learning (SEL). Philosophy-based character education plays a significant preventive role in reducing bullying by strengthening moral values, empathy, and the development of ethical and inclusive school climates.